Phosphorus-containing sewage treatment method based on local controllable release of iron ions

By using conductive bacterial cellulose composite materials with solid iron atoms to release iron ions during the electrolysis process, the phosphate ions in the wastewater react with the iron ions to form iron phosphate precipitation, which solves the problem of low treatment efficiency and sludge in the prior art The problem of difficulty in dealing with the problem of difficulty in recycling phosphorus resources has been achieved, and efficient and resource-based phosphorus removal effect has been achieved.

CN119409291AActive Publication Date: 2025-02-11HANGZHOU NORMAL UNIVERSITY
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510014492.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The existing biological phosphorus removal technology has low treatment efficiency and is difficult to treat sludge. However, chemical phosphorus removal technology requires the addition of chemical agents, is expensive and difficult to treat sludge. Both technologies are difficult to achieve resource utilization of phosphorus elements.

Method used

Using conductive bacterial cellulose composite material with solid iron atoms as the anode, iron ions are released in local supersaturation through the electrolysis process, so that the phosphate ions in the wastewater react with the iron ions to form iron phosphate precipitation, realizing the in-situ of phosphorus Deposition and resource utilization.

Benefits of technology

It has achieved efficient removal of phosphorus in sewage, avoided the use of chemical agents and the formation of chemical sludge, solved the problem of difficult sludge treatment and difficult recovery of phosphorus resources, and the process is controllable and resource utilization is significant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409291A_ABST
    Figure CN119409291A_ABST
Patent Text Reader

Abstract

The invention discloses a phosphorus-containing sewage treatment method based on local controllable release of iron ions. The method comprises the following steps: taking a conductive bacterial cellulose composite material immobilized with iron atoms as an anode; adding the anode and the cathode into phosphorus-containing sewage and electrifying to enable the anode to release iron ions; phosphorus phosphate in phosphorus-containing sewage reacts with iron ions on the surface of the anode to form a precipitate which is enriched and deposited on the anode in situ. The conductive bacterial cellulose is selected as a fixed carrier of iron atoms, efficient dispersion of iron is realized, the iron is controllably converted into iron ions, phosphorus in sewage is deposited in a three-dimensional network structure of the bacterial cellulose in a form of iron phosphate in a local supersaturated state, formation of chemical sludge is avoided, subsequent treatment of the sewage is not needed, and the method is simple and convenient. And the purposes of synchronously removing phosphorus and realizing resource utilization of phosphorus are achieved. In the treatment process, chemical agents do not need to be added, and chemical sludge is not generated, so that the problems of secondary pollution, high treatment difficulty of the generated sludge and the like are fundamentally solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of industrial and agricultural wastewater treatment, and specifically relates to a method for treating phosphorus-containing wastewater based on the local controlled release of iron ions. Background Art

[0002] The rapid development of modern industry and agriculture has significantly improved the living standards of human beings, but in the process, a series of environmental pollution problems have also arisen, and the problems caused by the discharge of industrial and agricultural wastewater containing nutrients such as phosphorus and nitrogen are typical. Studies have shown that phosphorus is the main pollutant causing eutrophication of water bodies. When the total phosphorus content in water reaches 0.015 mg / L, it can cause eutrophication of water bodies. While emphasizing the urgent need to control phosphorus pollutants in water bodies, it should also be noted that phosphorus is an important resource necessary for industrial and agricultural development and even life activities. However, phosphorus belongs to the sedimentary cycle in the geochemical cycle and is a non-renewable resource facing exhaustion. Therefore, researching and developing new technologies that take into account the treatment of phosphorus-containing wastewater and its resource recycling is an urgent issue in this field.

[0003] At present, urban sewage treatment plants generally use biological phosphorus removal technology to treat phosphorus-containing aquaculture sewage and domestic sewage. It is achieved by excessive absorption of soluble phosphates in the water by microorganisms and is treated in the form of residual sludge. This process is time-consuming and not only leads to a waste of phosphorus resources, but also easily causes secondary pollution when it flows into surface water and groundwater, and aggravates the eutrophication of water bodies. More importantly, biological phosphorus removal technology is generally only applicable to low-concentration phosphorus-containing sewage. With the gradual improvement of sewage discharge standards, a single biological phosphorus removal process is difficult to meet the corresponding requirements of the standards.

[0004] Chemical phosphorus removal is another method for treating phosphorus-containing wastewater besides biological phosphorus removal. It achieves the purpose of phosphorus removal by adding chemical agents to the sewage, causing them to react chemically with phosphates in the water body and form precipitation. It can be regarded as an artificial enhancement of phosphate precipitation in nature. However, there are still some difficult problems in chemical phosphorus removal technology: First, in the chemical treatment process, the amount of chemical agents added is difficult to accurately control. In order to achieve the ideal phosphorus removal effect, it is generally required to add excessive metal salt agents, which is bound to lead to new water pollution problems and increase the overall treatment cost due to unnecessary waste of agents. Second, the chemical phosphorus removal process will form a large amount of chemical sludge, which is difficult to handle later. In addition, the traditional chemical method still fails to overcome the disadvantage that phosphorus resources are difficult to recycle. It takes a lot of manpower and material resources to separate it from sewage and recycle it. Summary of the invention

[0005] The purpose of the present invention is to provide a novel phosphorus-containing sewage treatment method and a conductive bacterial cellulose composite material with iron atoms immobilized therein for the existing biological phosphorus removal technology, which forms a large amount of residual sludge, has low treatment efficiency, and is only applicable to low-concentration sewage, while the chemical phosphorus removal technology requires artificial addition of chemical agents, high treatment costs, and great difficulty in subsequent treatment of chemical sludge. At the same time, both technologies are prone to secondary pollution and are difficult to realize the resource utilization of phosphorus elements. The present invention can efficiently remove phosphorus from sewage and realize its resource utilization, and no chemical agent needs to be added during the process and no chemical sludge is generated, which fundamentally solves the problems that conventional biological and chemical technologies are prone to secondary pollution, the generated sludge is difficult to treat, and phosphorus resources in phosphorus-containing sewage are difficult to recycle. The present invention selects conductive bacterial cellulose as a fixed carrier of iron atoms, realizes efficient dispersion of iron, makes it controllably converted into iron ions, and deposits phosphorus in sewage in the form of iron phosphate in situ in the three-dimensional network structure of bacterial cellulose in a locally supersaturated state, avoids the formation of chemical sludge, and does not need to perform subsequent treatment on sewage, so as to achieve the purpose of synchronous phosphorus removal and phosphorus resource utilization.

[0006] In the first aspect, the present invention provides a method for treating phosphorus-containing wastewater based on the local controlled release of iron ions, and the treatment process is as follows: a conductive bacterial cellulose composite material that immobilizes iron atoms is used as an anode; the anode and the cathode are added to the phosphorus-containing wastewater and energized, so that the anode releases iron ions, and a state of local supersaturation of iron ions is formed around the anode; the phosphate ions in the phosphorus-containing wastewater react with the iron ions on the surface of the anode to form a precipitate that is enriched and deposited in situ on the anode.

[0007] The conductive bacterial cellulose composite material with fixed iron atoms is prepared by preparing a bacterial cellulose culture medium, inoculating film-forming bacteria for cultivation, adding a pyrrole solution to the culture medium after bacterial cellulose is produced, and continuing the cultivation, and successively immersing the obtained product in a potassium persulfate solution, a ferrous chloride solution, and a sodium borohydride solution for reaction.

[0008] Preferably, the voltage applied to the anode and cathode is 0.1 V to 0.8 V.

[0009] Preferably, the cathode is made of stainless steel, such as 304 or 316 stainless steel sheet.

[0010] Preferably, the conductivity of the conductive bacterial cellulose composite material with immobilized iron atoms is 20 S / m to 1600 S / m, and the mass fraction of iron atoms in the composite material is 0.40 wt% to 3.50 wt%.

[0011] As a preference, the initial phosphate phosphorus value (PO 4 3- -P) is 50 mg / L~1000 mg / L.

[0012] Preferably, after the phosphorus-containing wastewater treatment is completed or the iron phosphate precipitate attached to the conductive bacterial cellulose composite material reaches a preset amount, the conductive bacterial cellulose composite material carrying iron atoms as the anode is taken out and the iron phosphate precipitate on the anode is recovered.

[0013] Preferably, the iron phosphate recovered from the anode is used as a precursor for preparing lithium iron phosphate, a positive electrode material for lithium-ion batteries.

[0014] In a second aspect, the present invention provides a method for preparing a conductive bacterial cellulose composite material immobilized with iron atoms, comprising the following steps: Step 1: Prepare bacterial cellulose culture medium and inoculate film-forming bacteria for cultivation.

[0015] Step 2: Add the pyrrole solution into the bacterial cellulose culture medium and continue culturing.

[0016] Step 3: Take out the product obtained in step 2, immerse it in a potassium persulfate solution, and react.

[0017] Step 4: Take out the product obtained in step 3, wash it, immerse it in ferrous chloride solution, and perform ultrasonic treatment for 0.5 h to 5 h.

[0018] Step 5: Immerse the product obtained in step 4 in a sodium borohydride solution for reaction. After the reaction is completed, take out the solid product and wash it to obtain a conductive bacterial cellulose composite material with iron atoms immobilized thereon.

[0019] Preferably, in step 1, the bacterial cellulose culture medium is a mixed solution of glucose, peptone, yeast extract, disodium hydrogen phosphate and ethanol. The mass concentrations of glucose, peptone, yeast extract, disodium hydrogen phosphate and ethanol in the mixed solution are 4% to 10%, 0.4% to 1.2%, 0.4% to 1.2%, 0.02% to 0.1% and 0.02% to 0.1%, respectively; the film-forming bacteria is Acetobacter xylinum; the culture conditions are: culture temperature 25 ℃ to 35 ℃, culture time 3 days.

[0020] Preferably, in step 2, the pyrrole solution is a solution obtained by dissolving pyrrole and nonylphenol polyoxyethylene ether in deionized water; in the pyrrole solution, the mass fraction of pyrrole is 0.2 wt% to 2 wt%, and the mass ratio of pyrrole to nonylphenol polyoxyethylene ether is 5:1 to 1:1.2; and the culture conditions are: culture temperature 25°C to 35°C, and culture time 4d to 8d.

[0021] Preferably, in step three, the concentration of the potassium persulfate solution is 2 g / L to 20 g / L; the reaction conditions are: reaction temperature 0°C to 4°C, and reaction time 4 h to 16 h.

[0022] Preferably, in step 4, the cleaning process is: cleaning with 0.02 mol / L hydrochloric acid solution, 0.02 mol / L sodium hydroxide solution, 75% ethanol aqueous solution and deionized water in sequence; the concentration of the ferrous chloride solution is 0.05 mol / L to 0.5 mol / L.

[0023] Preferably, in step five, the concentration of the sodium borohydride solution is 0.10 mol / L to 0.50 mol / L; the reaction conditions are: reaction temperature 20°C to 80°C, reaction time 2 h to 12 h.

[0024] In a third aspect, the present invention provides a conductive bacterial cellulose composite material immobilized with iron atoms, which is prepared by the aforementioned preparation method; Preferably, the conductivity of the conductive bacterial cellulose composite material with immobilized iron atoms is 20 S / m to 1600 S / m, and the mass fraction of iron atoms in the composite material is 0.40 wt% to 3.50 wt%.

[0025] Compared with the prior art, the present invention has the following beneficial effects.

[0026] 1. The present invention uses a conductive bacterial cellulose composite material with fixed iron atoms to treat phosphorus-containing sewage in the industrial and agricultural fields. The composite material can generate iron ions in situ, and in a local supersaturated state, the generated iron ions react chemically with the phosphates diffused and adsorbed to the composite material to form iron phosphate and deposit it in situ on the composite material, thereby achieving the purpose of phosphorus-containing sewage treatment and phosphorus resource utilization. The whole process does not require the addition of chemical agents and does not produce chemical sludge, fundamentally solving the problems of secondary pollution caused by conventional biological and chemical technologies, difficulty in treating the generated sludge, and difficulty in recovering phosphorus resources in phosphorus-containing sewage.

[0027] 2. The present invention selects conductive bacterial cellulose as a fixed carrier of iron atoms, realizes efficient dispersion of iron, enables controllable conversion of iron ions, and can freely regulate the occurrence and termination of the reaction.

[0028] 3. The present invention makes full use of the specific three-dimensional network structure and high affinity of bacterial cellulose. Phosphates in sewage can be easily diffused and adsorbed to the composite material. Iron ions and phosphates are in a locally supersaturated state to generate iron phosphate and are deposited in situ on the composite material, avoiding the formation of chemical sludge and the difficulty of subsequent treatment.

[0029] 4. The iron phosphate obtained by resource treatment of phosphorus-containing wastewater in the present invention can be used as a precursor of lithium iron phosphate, a positive electrode material of lithium-ion batteries, after dehydration treatment, and can also be widely used as an adsorbent, catalyst, anti-rust pigment and additive. At the same time, the hydrogen generated in the process of phosphorus-containing wastewater treatment in the present invention can also be used as a fuel, a reducing agent and a chemical raw material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the curve of the change of phosphate phosphorus (PO43--P) value in sewage with reaction time.

[0031] Figure 2 The mass changes of anode and cathode before and after the reaction.

[0032] Figure 3 Field emission scanning electron microscopy comparison of the conductive bacterial cellulose composite material with immobilized iron atoms before (a) and after (b) the reaction.

[0033] Figure 4 It is a comparison chart of the phosphate removal effects corresponding to Example 1 of the present invention and Comparative Examples 1-3.

[0034] Figure 5 The influence of circuit connectivity on the treatment results during the treatment of phosphorus-containing wastewater by conductive bacterial cellulose composite materials with immobilized iron atoms.

[0035] Figure 6 These are the test results of the recycling treatment of phosphorus-containing wastewater using conductive bacterial cellulose composite materials that immobilize iron atoms. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Example 1

[0038] A method for treating phosphorus-containing wastewater, the process of which is: using a conductive bacterial cellulose composite material with iron atoms immobilized as an anode and stainless steel as a cathode, electrifying the phosphorus-containing wastewater. During the electrolysis process, the composite material as the anode releases iron ions, forming a state of local supersaturation of iron ions, so that phosphate ions in the water body combine with iron ions on the surface of the anode to form iron phosphate precipitation deposited in situ on the anode; at the same time, the state of local supersaturation of iron ions promotes the formation of iron phosphate precipitation.

[0039] In this embodiment, the sizes of the anode and cathode are both 1 cm by 1 cm to 5 cm by 5 cm; the anode and cathode are arranged opposite to each other with a spacing of 1 cm to 10 cm; and the voltage applied between the anode and cathode is 0.1 V to 0.8 V.

[0040] The iron phosphate on the anode can be recycled as a precursor of lithium iron phosphate, a positive electrode material for lithium-ion batteries, and can also be widely used as an adsorbent, catalyst, anti-rust pigment and additive. The iron phosphate precipitate on the composite material can be recycled by gently scraping it off.

[0041] The preparation method of the conductive bacterial cellulose composite material with fixed iron atoms comprises the following steps: (1) Weigh 15.00 g glucose, 1.20 g peptone, 1.20 g yeast extract, 0.075 g disodium hydrogen phosphate and 0.075 g ethanol respectively and dissolve them in 150 mL deionized water to prepare bacterial cellulose culture medium. Inoculate Acetobacter xylinum into the culture medium and culture it at 30 °C for 3 days to produce bacterial cellulose film.

[0042] (2) Weigh 0.10 g of pyrrole and 0.050 g of nonylphenol polyoxyethylene ether respectively, dissolve in 10 mL of deionized water to prepare a pyrrole solution. Add the obtained pyrrole solution to the culture medium containing bacterial cellulose membrane obtained in step (1), and continue to culture at 30°C for 5 days to allow the bacterial cellulose membrane to continue to grow and introduce pyrrole into the bacterial cellulose membrane.

[0043] (3) Take out the product obtained in step (2), immerse it in a potassium persulfate solution with a concentration of 10 g / L, and react at 0°C for 8 h.

[0044] (4) Take out the product obtained in step (3), wash it with 0.02 mol / L hydrochloric acid solution, 0.02 mol / L sodium hydroxide solution, 75% ethanol aqueous solution and deionized water in sequence, and then immerse it in 0.10 mol / L ferrous chloride solution and ultrasonicate it for 2 h.

[0045] (5) The product obtained in step (4) is immersed in a sodium borohydride solution with a concentration of 0.20 mol / L and reacted at 60°C for 4 hours. After the reaction is completed, the solid is taken out and washed with deionized water to obtain a conductive bacterial cellulose composite material with iron atoms immobilized thereon. The composite material comprises bacterial cellulose, polypyrrole loaded on the bacterial cellulose, and iron atoms loaded on the polypyrrole.

[0046] According to the test, the conductivity of the conductive bacterial cellulose composite material with immobilized iron atoms obtained in this example is 800 S / m, and the mass fraction of iron atoms in the composite material is 2.50 wt%.

[0047] The conductive bacterial cellulose composite material with immobilized iron atoms obtained in this embodiment can be used for resource utilization of phosphorus-containing wastewater. In order to prove the effect of the composite material prepared in this embodiment on treating phosphorus-containing wastewater, the following experiment was carried out: Experimental group: 1000 mL of sewage from the supernatant of a primary sedimentation tank of a rural farm was collected. 4 3- -P, the phosphate phosphorus value specifically indicates the concentration of all inorganic phosphorus in terms of phosphate. ) value is 120 mg / L, and the sewage is used as the phosphorus-containing sewage to be treated. Take 3 cm´3 cm of a conductive bacterial cellulose composite material with immobilized iron atoms obtained in this embodiment and 3 cm´3 cm of a stainless steel sheet; then use the two as anode and cathode, respectively, and connect the positive and negative electrodes of a DC regulated power supply, respectively. The two electrodes are arranged oppositely with a spacing of 4 cm, and the reaction temperature is controlled to be 30 °C. Power is turned on and the control voltage is 0.4 V. During the reaction, the phosphate phosphorus (PO 4 3- -P) value changes with reaction time as shown in Figure 1 After 4 h of reaction, the phosphate content of the wastewater (PO 4 3- -P) value decreased by 95.26%. Before and after the experiment, the quality of the anode and cathode (after cleaning and drying) changed as follows Figure 2 As shown, the anode mass increased by 0.4722 g, while the cathode mass remained basically unchanged.

[0048] The microscopic comparison of the anode surface before and after the test is as follows: Figure 3 shown by Figure 3 As can be seen from part (a) of the graph, the fiber size of the conductive bacterial cellulose composite material with immobilized iron atoms before the experiment was about tens of nanometers, and the holes formed by the accumulation between the fibers were clearly visible. Figure 3 As can be seen from part (b) of the graph, the reacted composite material after the test becomes significantly denser, and a large number of pores are covered thereon, which is caused by the formation of solid precipitation and in-situ deposition on the composite material.

[0049] In order to determine the changes in the iron atoms in the anode, the anode was taken out after being energized for 1 hour, placed in deionized water and vigorously shaken for 1 hour. Dilute sulfuric acid was added to the solution obtained after shaking to adjust the pH to 2, and then an acidic potassium permanganate solution was added. The purple-red color did not fade, indicating that the solution did not contain ferrous ions; potassium thiocyanate solution was added to the solution obtained after shaking, and the solution turned red, indicating that the solution contained iron ions. By calculating the phosphate phosphorus (PO4) before and after the treatment of phosphorus-containing wastewater, the phosphorus content of the phosphate phosphorus (PO4) was calculated. 4 3- -P) decrease and anode mass increase, combined with the color reaction, confirmed that FePO 4×2H 2 Formation and in-situ deposition of O at the anode.

[0050] At the same time, bubbles can be observed at the cathode. When the methylene blue-platinum reagent is dropped into the cathode solution, the blue color gradually fades, which shows that the gas generated at the cathode is reducing hydrogen.

[0051] Based on the above experimental results, it can be inferred that during the reaction process, the anode and cathode undergo the following reactions respectively: anode:

[0052] cathode: Comparative Example 1 A method for treating phosphorus-containing wastewater. The difference between this comparative example and Example 1 is that the anode used is different; the difference between the preparation process of the anode used in this example and the conductive bacterial cellulose composite material with immobilized iron atoms used in Example 1 is that pyrrole is not added in step (2), and the composite material finally obtained does not contain polypyrrole and is not conductive.

[0053] This comparative example conducts a phosphorus-containing wastewater treatment experiment, as control group 1, and the experimental conditions other than the anode are the same as those of the experimental group in Example 1. After 4 hours of action, the phosphorus phosphate (PO 4 3- -P) value decreased by 6.36% (see Figure 4 ), and the quality of the composite material did not change basically before and after the experiment.

[0054] Comparative Example 2 A method for treating phosphorus-containing wastewater. The difference between this comparative example and comparative example 1 is that no voltage is applied during the treatment process.

[0055] This comparative example conducts a phosphorus-containing wastewater treatment experiment, and as control group 2, except that no voltage is applied, other experimental conditions remain the same as those of control group 1 in comparative example 1. After 4 hours of action, the phosphorus phosphate (PO 4 3- -P) value decreased by 6.22% (see Figure 4 ), and the quality of the composite material did not change substantially before and after the experiment. Comparative Examples 1 and 2 show that the non-conductive bacterial cellulose composite material with iron atoms only has a certain adsorption effect on phosphorus-containing wastewater, and phosphorus phosphate (PO 4 3- The decrease in the value of -P) has nothing to do with the electrochemical reaction.

[0056] Comparative Example 3 A method for treating phosphorus-containing wastewater. The difference between this comparative example and Example 1 is that the anode used is different; the difference between the preparation process of the anode used in this example and the conductive bacterial cellulose composite material with immobilized iron atoms used in Example 1 is that no ferrous chloride solution is used in steps (2) and (4), and the composite material finally obtained does not contain iron.

[0057] This comparative example conducts a phosphorus-containing wastewater treatment experiment as control group 3; except for the anode, the other experimental conditions are the same as those of the experimental group in Example 1. After 4 hours of action, the phosphorus phosphate (PO 4 3- -P) value decreased by 5.94% (see Figure 4 ), and the quality of the composite material did not change basically before and after the experiment.

[0058] Example 2

[0059] A method for treating phosphorus-containing wastewater. The difference between this comparative example and Example 1 is that the dosage and reaction conditions of some substances in the preparation method of the conductive bacterial cellulose composite material for immobilizing iron atoms as an anode are different.

[0060] The method for preparing the conductive bacterial cellulose composite material immobilized with iron atoms in this embodiment comprises the following steps: (1) Weigh 15.00 g glucose, 1.20 g peptone, 1.20 g yeast extract, 0.075 g disodium hydrogen phosphate and 0.075 g ethanol respectively and dissolve them in 150 mL deionized water to prepare bacterial cellulose culture medium. Inoculate Acetobacter xylinum into the culture medium and culture it at 30 °C for 3 days to produce bacterial cellulose film.

[0061] (2) Weigh 0.25 g of pyrrole and 0.050 g of nonylphenol polyoxyethylene ether respectively, dissolve in 10 mL of deionized water to prepare a pyrrole solution. Add the obtained pyrrole solution to the mixed solution containing bacterial cellulose membrane obtained in step (1), and continue to culture at 30°C for 5 days to allow the bacterial cellulose membrane to continue to grow and introduce pyrrole into the bacterial cellulose membrane.

[0062] (3) Take out the product obtained in step (2), immerse it in a potassium persulfate solution with a concentration of 10 g / L, and react at 0°C for 8 h.

[0063] (4) The product obtained in step (3) was taken out and washed with 0.02 mol / L hydrochloric acid solution, 0.02 mol / L sodium hydroxide solution, 75% ethanol aqueous solution and deionized water in sequence, and then immersed in 0.10 mol / L ferrous chloride solution and ultrasonicated for 2 h.

[0064] (5) The product obtained in step (4) was immersed in a sodium borohydride solution with a concentration of 0.20 mol / L and reacted at 60°C for 4 hours. After the reaction, the solid was taken out and washed with deionized water to obtain a conductive bacterial cellulose composite material with immobilized iron atoms. The conductivity of the obtained conductive bacterial cellulose composite material with immobilized iron atoms was 1400 S / m, and the mass fraction of iron atoms in the composite material was 2.28 wt%.

[0065] The conductive bacterial cellulose composite material with iron atoms immobilized in this example was used for resource utilization of phosphorus-containing wastewater. The experimental conditions were the same as those of the experimental group in Example 1. After 4 h of reaction, the phosphorus phosphate (PO 4 3- -P) value decreased by 97.27%, and 0.4826 g of FePO was collected at the anode. 4 ×2H 2 O, showing excellent removal and resource utilization effects of phosphorus-containing wastewater.

[0066] In order to verify that the present invention has unique controllability in treating phosphorus-containing wastewater, the power was turned off after the reaction lasted for a certain period of time, and the phosphorus phosphate (PO 4 3- -P) value changes with reaction time (see Figure 5 ).Depend on Figure 5 It can be seen that when the circuit is connected, the phosphate phosphorus (PO 4 3- -P) value decreased significantly as the reaction proceeded; after power failure, the phosphate phosphorus (PO 4 3- -P) value remains basically unchanged; after power is restored, the phosphate phosphorus (PO 4 3- -P) value began to decrease again; after the power was cut off again, the phosphate phosphorus (PO 4 3- -P) value no longer changes. This result shows that the phosphorus-containing wastewater treatment technology used in the present invention can freely regulate the occurrence and termination of the reaction. In the actual treatment process, when the phosphorus phosphate (PO 4 3- -P) value reaches the target value, the reaction can be terminated by simply cutting off the power, which fundamentally solves the defect of chemical phosphorus removal technology that chemical agents are difficult to control accurately and easily cause many subsequent problems.

[0067] Example 3

[0068] A method for treating phosphorus-containing wastewater. The difference between this comparative example and Example 1 is that the dosage and reaction conditions of some substances in the preparation method of the conductive bacterial cellulose composite material for immobilizing iron atoms as an anode are different.

[0069] The method for preparing the conductive bacterial cellulose composite material immobilized with iron atoms in this embodiment comprises the following steps: (1) Weigh 15.00 g glucose, 1.20 g peptone, 1.20 g yeast extract, 0.075 g disodium hydrogen phosphate and 0.075 g ethanol respectively and dissolve them in 150 mL deionized water to prepare bacterial cellulose culture medium. Inoculate Acetobacter xylinum into the culture medium and culture it at 30 °C for 3 days to produce bacterial cellulose film.

[0070] (2) Weigh 0.10 g of pyrrole and 0.050 g of nonylphenol polyoxyethylene ether respectively, dissolve in 10 mL of deionized water to prepare a pyrrole solution. Add the obtained pyrrole solution to the mixed solution containing bacterial cellulose membrane obtained in step (1), and continue to culture at 30°C for 5 days to allow the bacterial cellulose membrane to continue to grow and introduce pyrrole into the bacterial cellulose membrane.

[0071] (3) Take out the product obtained in step (2), immerse it in a potassium persulfate solution with a concentration of 10 g / L, and react at 0°C for 8 h.

[0072] (4) The product obtained in step (3) was taken out and washed with 0.02 mol / L hydrochloric acid solution, 0.02 mol / L sodium hydroxide solution, 75% ethanol aqueous solution and deionized water in sequence, and then immersed in 0.30 mol / L ferrous chloride solution and ultrasonicated for 2 h.

[0073] (5) The product obtained in step (4) was immersed in a sodium borohydride solution with a concentration of 0.20 mol / L and reacted at 60°C for 4 hours. After the reaction, the solid was taken out and washed with deionized water to obtain a conductive bacterial cellulose composite material with immobilized iron atoms. The conductivity of the obtained conductive bacterial cellulose composite material with immobilized iron atoms was 920 S / m, and the mass fraction of iron atoms in the composite material was 3.50 wt%.

[0074] The conductive bacterial cellulose composite material with iron atoms immobilized in this example was used for resource utilization of phosphorus-containing wastewater. The experimental conditions were the same as those of the experimental group in Example 1. After 4 h of reaction, the phosphorus phosphate (PO 4 3- -P) value decreased by 98.62%, and 0.4877 g of FePO was collected at the anode. 4 ×2H 2 O, showing excellent removal and resource utilization effects of phosphorus-containing wastewater.

[0075] In order to investigate the recycling treatment capacity of the obtained conductive bacterial cellulose composite material with immobilized iron atoms for phosphorus-containing wastewater, the used conductive bacterial cellulose composite material with immobilized iron atoms was taken out from the reaction solution, washed with deionized water and used again for phosphorus-containing wastewater treatment, and the experimental conditions remained unchanged. Figure 6 As shown in the figure, after five cycles of use, a conductive bacterial cellulose composite material immobilized with iron atoms can still degrade phosphate phosphorus (PO 4 3- -P) value decreased by 96.79%, indicating that the obtained conductive bacterial cellulose composite material with immobilized iron atoms has excellent recycling treatment ability for phosphorus-containing wastewater.

[0076] Example 4

[0077] A method for treating phosphorus-containing wastewater. The difference between this comparative example and Example 1 is that the dosage and reaction conditions of some substances in the preparation method of the conductive bacterial cellulose composite material for immobilizing iron atoms as an anode are different.

[0078] The method for preparing the conductive bacterial cellulose composite material immobilized with iron atoms in this embodiment comprises the following steps: (1) Weigh 15.00 g glucose, 1.20 g peptone, 1.20 g yeast extract, 0.075 g disodium hydrogen phosphate and 0.075 g ethanol respectively and dissolve them in 150 mL deionized water to prepare bacterial cellulose culture medium. Inoculate Acetobacter xylinum into the culture medium and culture it at 30 °C for 3 days to produce bacterial cellulose film.

[0079] (2) Weigh 0.20 g of pyrrole and 0.050 g of nonylphenol polyoxyethylene ether respectively, dissolve in 10 mL of deionized water to prepare a pyrrole solution. Add the obtained pyrrole solution to the mixed solution containing bacterial cellulose membrane obtained in step (1), and continue to culture at 30°C for 5 days to allow the bacterial cellulose membrane to continue to grow and introduce pyrrole into the bacterial cellulose membrane.

[0080] (3) Take out the product obtained in step (2), immerse it in a potassium persulfate solution with a concentration of 10 g / L, and react at 0°C for 8 h.

[0081] (4) The product obtained in step (3) was taken out and washed with 0.02 mol / L hydrochloric acid solution, 0.02 mol / L sodium hydroxide solution, 75% ethanol aqueous solution and deionized water in sequence, and then immersed in 0.20 mol / L ferrous chloride solution and ultrasonicated for 2 h.

[0082] (5) The product obtained in step (4) was immersed in a sodium borohydride solution with a concentration of 0.20 mol / L and reacted at 60°C for 4 hours. After the reaction, the solid was taken out and washed with deionized water to obtain a conductive bacterial cellulose composite material with immobilized iron atoms. The conductivity of the obtained conductive bacterial cellulose composite material with immobilized iron atoms was 920 S / m, and the mass fraction of iron atoms in the composite material was 2.96 wt%.

[0083] The conductive bacterial cellulose composite material with iron atoms immobilized in this example was placed in 10 L of initial phosphate (PO 4 3- -P) value of 1000 mg / L in phosphorus-containing wastewater, and then the phosphate phosphorus (PO 4 3- -P) value no longer changes, indicating that the iron atoms in the composite material have been exhausted. The composite material was taken out of the reaction solution, washed with deionized water, and immersed in a 0.10 mol / L ferrous chloride solution for ultrasonic treatment for 2 h. The obtained product was then immersed in a 0.20 mol / L sodium borohydride solution and reacted at 60 °C for 4 h. After the reaction, the solid was taken out and washed with deionized water to obtain a conductive bacterial cellulose composite material with iron atoms immobilized. The conductivity of the obtained conductive bacterial cellulose composite material with iron atoms immobilized is 770 S / m, and the mass fraction of iron atoms in the composite material is 2.58 wt%.

[0084] The conductive bacterial cellulose composite material with re-immobilized iron atoms was used for resource utilization of phosphorus-containing wastewater, and the experimental conditions were the same as those of the experimental group in Example 1. After 4 h of reaction, the phosphorus phosphate (PO 4 3- -P) value decreased by 96.88%, and 0.4791 g of FePO was collected at the anode. 4 ×2H 2 O. The above experimental results show that the conductive bacterial cellulose composite material with iron atoms immobilized on it obtained by the present invention has excellent regeneration performance.

[0085] Example 5

[0086] A method for treating phosphorus-containing wastewater. The difference between this comparative example and Example 1 is that the dosage and reaction conditions of some substances in the preparation method of the conductive bacterial cellulose composite material for immobilizing iron atoms as an anode are different.

[0087] The method for preparing the conductive bacterial cellulose composite material immobilized with iron atoms in this embodiment comprises the following steps: (1) Weigh 15.00 g glucose, 1.20 g peptone, 1.20 g yeast extract, 0.075 g disodium hydrogen phosphate and 0.075 g ethanol respectively and dissolve them in 150 mL deionized water to prepare bacterial cellulose culture medium. Inoculate Acetobacter xylinum into the culture medium and culture it at 30 °C for 3 days to produce bacterial cellulose film.

[0088] (2) Weigh 0.15 g of pyrrole and 0.10 g of nonylphenol polyoxyethylene ether respectively, dissolve in 10 mL of deionized water to prepare a pyrrole solution. Add the obtained pyrrole solution to the mixed solution containing bacterial cellulose membrane obtained in step (1), and continue to culture at 30°C for 5 days to allow the bacterial cellulose membrane to continue to grow and introduce pyrrole into the bacterial cellulose membrane.

[0089] (3) Take out the product obtained in step (2), immerse it in a potassium persulfate solution with a concentration of 8 g / L, and react at 0°C for 6 h.

[0090] (4) The product obtained in step (3) was taken out and washed with 0.02 mol / L hydrochloric acid solution, 0.02 mol / L sodium hydroxide solution, 75% ethanol aqueous solution and deionized water in sequence, and then immersed in 0.15 mol / L ferrous chloride solution and ultrasonicated for 2 h.

[0091] (5) The product obtained in step (4) was immersed in a sodium borohydride solution with a concentration of 0.20 mol / L and reacted at 60°C for 4 hours. After the reaction, the solid was taken out and washed with deionized water to obtain a conductive bacterial cellulose composite material with immobilized iron atoms. The conductivity of the obtained conductive bacterial cellulose composite material with immobilized iron atoms was 860 S / m, and the mass fraction of iron atoms in the composite material was 2.46 wt%.

[0092] The conductive bacterial cellulose composite material with iron atoms immobilized in this embodiment is used for resource utilization of phosphorus-containing wastewater. In order to prove the effect of the composite material prepared in this embodiment on treating phosphorus-containing wastewater, the following experiment is carried out: Experimental group: 1000 mL of industrial wastewater from a chemical plant was collected. 4 3- -P) value was 525 mg / L, and the wastewater was used as the phosphorus-containing wastewater to be treated. Other experimental conditions were the same as those of the experimental group in Example 1. After 6 h of reaction, the phosphate phosphorus (PO 4 3- -P) value decreased by 96.21%, and 2.0136 g of FePO was collected at the anode. 4 ×2H 2 O, showing excellent removal and resource utilization effects of phosphorus-containing wastewater.

[0093] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of implementation of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.

Claims

1. A method for treating phosphorus-containing wastewater based on local controlled release of iron ions, characterized in that: A conductive bacterial cellulose composite material with immobilized iron atoms is used as the anode; phosphorus-containing wastewater is added to the anode and cathode and electricity is applied, so that the anode releases iron ions and a state of local supersaturation of iron ions is formed around the anode; phosphate ions in the phosphorus-containing wastewater react with iron ions on the anode surface to form a precipitate that is enriched and deposited in situ on the anode; The conductive bacterial cellulose composite material with fixed iron atoms is prepared by preparing a bacterial cellulose culture medium, inoculating film-forming bacteria for cultivation, adding a pyrrole solution to the culture medium after bacterial cellulose is produced, and continuing the cultivation, and successively immersing the obtained product in a potassium persulfate solution, a ferrous chloride solution, and a sodium borohydride solution for reaction.

2. A method for treating phosphorus-containing wastewater based on local controlled release of iron ions according to claim 1, characterized in that: The voltage applied to the anode and cathode is 0.1 V to 0.8 V.

3. A method for treating phosphorus-containing wastewater based on local controlled release of iron ions according to claim 1, characterized in that: The conductivity of the conductive bacterial cellulose composite material with iron atoms immobilized thereon is 20 S / m to 1600 S / m, and the mass fraction of iron atoms in the composite material is 0.40 wt% to 3.50 wt%.

4. A method for treating phosphorus-containing wastewater based on local controlled release of iron ions according to claim 1, characterized in that: The initial phosphate phosphorus value of the phosphorus-containing wastewater is 50 mg / L to 1000 mg / L.

5. A method for treating phosphorus-containing wastewater based on local controlled release of iron ions according to claim 1, characterized in that: After the phosphorus-containing wastewater is treated, the conductive bacterial cellulose composite material that immobilizes iron atoms as the anode is taken out, and the iron phosphate precipitate on the anode is recovered.

6. A method for treating phosphorus-containing wastewater based on local controlled release of iron ions according to claim 5, characterized in that: The iron phosphate recovered from the anode is used as a precursor for preparing lithium iron phosphate, a positive electrode material for lithium-ion batteries.

7. A method for preparing a conductive bacterial cellulose composite material immobilized with iron atoms, characterized in that: The following steps are involved: Step 1: prepare bacterial cellulose culture medium and inoculate film-forming bacteria for cultivation; Step 2, adding the pyrrole solution into the bacterial cellulose culture medium and continuing the culture; Step 3, taking out the product obtained in step 2, immersing it in a potassium persulfate solution, and reacting; Step 4: Take out the product obtained in step 3, wash it, and then immerse it in ferrous chloride solution and ultrasonicate it for 0.5 h to 5 h; Step 5: Immerse the product obtained in step 4 in a sodium borohydride solution for reaction; after the reaction is completed, take out the solid product and wash it to obtain a conductive bacterial cellulose composite material with immobilized iron atoms.

8. The method for preparing a conductive bacterial cellulose composite material immobilized with iron atoms according to claim 7, characterized in that: In step 2, the pyrrole solution is a solution obtained by dissolving pyrrole and nonylphenol polyoxyethylene ether in deionized water; in the pyrrole solution, the mass fraction of pyrrole is 0.2 wt% to 2 wt%, and the mass ratio of pyrrole to nonylphenol polyoxyethylene ether is 5:1 to 1:1.2; the culture conditions are: culture temperature 25°C to 35°C, and culture time 4 d to 8 d.

9. The method for preparing a conductive bacterial cellulose composite material immobilized with iron atoms according to claim 7, characterized in that: In step 3, the concentration of the potassium persulfate solution is 2 g / L to 20 g / L, and the reaction conditions are: reaction temperature 0°C to 4°C, and reaction time 4 h to 16 h; in step 5, the concentration of the sodium borohydride solution is 0.10 mol / L to 0.50 mol / L, and the reaction conditions are: reaction temperature 20°C to 80°C, and reaction time 2 h to 12 h.

10. A conductive bacterial cellulose composite material with immobilized iron atoms, which is prepared by the preparation method as claimed in claim 7; the conductivity of the conductive bacterial cellulose composite material with immobilized iron atoms is 20 S / m to 1600 S / m, and the mass fraction of iron atoms in the composite material is 0.40 wt% to 3.50 wt%.

Citation Information

Patent Citations

  • Method for preparing polypyrrole coated bacterial cellulose nanometer electric-conduction composite material by utilizing bacterial cellulose as template

    CN102219997A

  • Bacterial cellulose film / nano-iron composite material and preparation method and application thereof

    CN108034067A

  • Cellulose carbon-based nano zero-valent iron material and preparation method thereof

    CN111943167A

  • Sewage nitrogen and phosphorus removal treatment method and device and application thereof

    CN112607847A

  • Integrated phosphorus recovery fuel cell device and wastewater treatment method

    CN113149148A